The Effect of Acetobacter xylinum Starter Concentration and Fermentation Time on the Quality of Nata de Pina - Agustin, Mila Aulina; Zulkifli, Lalu; Sedijani, Prapti; Sukarso, AA (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
The utilization of pineapple peel waste as a fermentation substrate has the potential to increase product value while reducing environmental pollution. One product that can be developed from this waste is nata de pina. This study aimed to analyze the effects of Acetobacter xylinum starter concentration and fermentation time on the quality of nata de pina. The research employed a quantitative experimental method using a Completely Randomized Design (CRD) with three replications. The treatments consisted of starter concentrations of 10%, 15%, and 20%, and fermentation periods of 8, 10, and 12 days. The observed parameters included nata thickness, yield, color, and texture. Data were analyzed using Two-Way ANOVA, and Tukey's post hoc test at a 5% significance level. The results showed that starter concentration and fermentation time significantly affect the thickness and yield of nata de pina with the results showing a significant effect (p < 0.05). The highest thickness (0.78 mm) and yield (48%) were obtained at a 20% starter concentration with 12 days of fermentation. The best color and texture were produced by nata de pina fermented with a 20% starter concentration for 10 days. Furthermore, The results showed no significant interaction between starter concentration and fermentation time on nata thickness (p > 0.05), whereas a significant interaction was observed for nata yield (p < 0.05). In conclusion, increasing the concentration of A. xylinum starter and extending fermentation time improved the physical quality of nata de pina, while the combination of a 20% starter concentration and 10 days of fermentation produced the best characteristics. These findings demonstrate the potential of pineapple peel waste as a sustainable raw material for producing value-added functional food.